Hydraulic fracture to enhance coalbed methane recovery by using coated ceramsite. Issue 6 (31st October 2022) - Zou, Mingjun; Yao, Linlin; Zhang, Miao; Huang, Zhiquan; Xu, Rongchao; Ding, Zibin; Zhang, Xingsheng
Abstract: In recent decades, coated ceramsite has become popular due to its low density, high compressive strength, and high flow conductivity, and it has been applied in many areas in construction field and chemical industry. In the area of hydraulic fracture, limited relevant literature can be found, especially on unconventional reservoirs with soft coals. In this paper, numerical simulation is performed to obtain migration regularity and granularity proportion using coated ceramsite, and it indicates that the biggest proppant concentration and strongest flow conductivity can be achieved under the granularity proportion of 1:6:2 with respective coated ceramsites of 40/60, 16/40, and 12/20 mesh. Then, a series of construction parameters are calculated and optimized to receive a best fracture performance by using mathematical methods, including total proppant volume, each proppant volume, fluid injection rate, fluid injection volume, and proppant concentration, etc. Results from micro seismic monitoring indicate that the actual fracture performance matches well with the simulated performance by using coated ceramsite and has an obviously longer fracture length and a bigger proppant concentration compared with performances by using quartz sand. Meanwhile, comparisons for gas productions fractured by coated ceramsite and quartz sand reveal that coated ceramsite can achieve a better drainage performance. All of the above can be a guide for hydraulic fracture and useful for enhancing coalbed methane recovery. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.